Diorganotin (IV) Complexes Aid Switch to Protect the Photodecomposition of PVC in Outdoor Buildings - Emad Yousif (Journal of Global Pharma Technology, 2019)
Three organotin (IV) complexes with different R-groups were used as additives for PVC. The photo-degradation rate constant of poly (vinyl chloride) upon irradiation with an ultraviolet light were investigated in the presence of Organotin(IV) complexes as photo stabilizers. Poly (vinyl chloride) photo-degradation rate constant was lower for the films containing Organotin (IV) complexes (5.6-1.5 × 10-3 sec-1) compared to the blank film (9.0 × 10-3 sec-1).Keywords: Organotin(IV), Photo stabilizers, UV irradiation, Poly(vinyl chloride), Photo degradation rate constant (kd).